Pengaruh sales promotion terhadap impulse buying konsumen - Rita Zahara (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
This research is conducted to analyze the influence of sales promotion on impulsive buying at ABC Hypermarket in East Jakarta. The aims of this research is also to know the sales promotion that influence the impulse buying, supporting factors and how the problems take place. The descriptive-verificative method is used in this research. Data collection methods are literature and field studies. Field study covers observation, interview and structural questionnaires. The questionnaires are given to 45 consumers at ABC Hypermarket in East Jakarta. The sistematic sampling is used as sampling technique. Data are analyzed by qualitative analysis and correlation regresion analysis. The analysis confirms that there are influences of sales promotion on impulse buying at ABC Hypermarket in West Jakarta. That is, if sales promotion is carefully done, it will increase impulse buying